Unmet needs and recommendations to improve meningioma care through patient, partner, and health care provider input: a mixed-method study. Issue 2 (2nd November 2019) - Zamanipoor Najafabadi, Amir H; van de Mortel, Johannes P M; Lobatto, Daniel J; Brandsma, Dieta R; Peul, Wilco C; Biermasz, Nienke; Taphoorn, Martin J B; Dirven, Linda; van Furth, Wouter R
Abstract: Background: It has been suggested that lack of ongoing registration of patient-centered outcomes has resulted in existing care trajectories that have not been optimized for sequelae experienced by meningioma patients. This study aimed to evaluate the structure of current meningioma care and identify issues and potential high-impact improvement initiatives. Methods: Using the grounded theory approach, a thematic framework was constructed based on the Dutch Comprehensive Cancer Organisation survey about issues in meningioma care trajectories. This framework was used during 3 semistructured interviews and 2 focus groups with patient-partner dyads (n = 16 participants), and 2 focus groups with health care providers (n = 11 participants) to assess issues in current meningioma care trajectories and possible solutions, including barriers to and facilitators for implementation. Results: Identified issues (n = 18 issues) were categorized into 3 themes: availability and provision of information, care and support, and screening for (neurocognitive) rehabilitation. A lack of information about the intervention and possible outcomes or complications, lack of support after treatment focusing on bodily and psychological functions, and reintegration into society were considered most important. Sixteen solutions were suggested, such as appointment of case managers (solution for 11/18 issues, 61%), assessment and treatment by physiatrists (22%), and routine use of patient-reported outcome measures for patient monitoring (17%). Barriers for these solutions were lack of budget, capacity, technology infrastructure, and qualified personnel with knowledge about issues experienced by meningioma patients. Conclusions: This study identified issues in current multidisciplinary meningioma care that are considered unmet needs by patients, partners, and health care providers and could guide innovation of care.